HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP TINGKAT KESIAPSIAGAAN MAHASISWA FAKULTAS ILMU KESEHATAN UPN VETERAN JAKARTA SEBAGAI CALON RELAWAN BENCANA GEMPA BUMI - Riski Dwiana (2021)
Preparedness is a series of activities to anticipate disasters through organizing and appropriate effective measures. Knowledge and attitude are included in the factors that influence preparedness. University students have an important obligation and role in disaster management to conduct well directed disaster management. The purpose of this study is to identify the relationship between knowledge and attitude level of preparedness in university students as prospective disaster volunteers. The design of this study was cross sectional with a descriptive survey type and used 229 students as samples. the quota sampling method used to calculate samples. The results of the analysis showed there is a relationship between knowledge and the level of preparedness with p value 0.001 (<0.05) and has a weak strength in a positive direction, while in the attitude analysis there is no relationship between attitudes and the level of preparedness with p value 0.371 (> 0,05) and the strength between attitude and level of preparedness is in the weak range with a positive direction. The conclusion of this study is that the higher the knowledge and attitude, the higher the level of student preparedness in dealing with disasters and preparing themselves as disaster volunteers, especially in the earthquake disaster